2023
DOI: 10.1111/ibi.13205
|View full text |Cite
|
Sign up to set email alerts
|

The importance of wetland habitat area for waterbird species‐richness

Abstract: The area of habitat patches is a significant factor when determining species-richness in any given habitat. However, this area effect is not the same for every taxonomic group and can change if is considered together with other habitat variables. The main objective of this study was to identify the importance of wetland area for waterbird speciesrichness when it is considered in conjunction with other habitat variables. Studies published in the Scopus and Web of Science databases in marine/coastal and inland w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 105 publications
0
2
0
Order By: Relevance
“…Vegetation is an important driver, providing food resources and hiding places; however, excessive vegetation cover can negatively affect waterbird survival [35]. Wetland area and shoreline length are strongly determinative of the extent of habitat in the fallow zone, which, as a confluence of aquatic and terrestrial ecosystems, provides a high diversity of niches and abundant food resources [13,41]. We found that all three of these factors were positively correlated with the species number and abundance of waterbirds within a certain range.…”
Section: Factors Affecting Waterbird Habitat Importancementioning
confidence: 99%
See 1 more Smart Citation
“…Vegetation is an important driver, providing food resources and hiding places; however, excessive vegetation cover can negatively affect waterbird survival [35]. Wetland area and shoreline length are strongly determinative of the extent of habitat in the fallow zone, which, as a confluence of aquatic and terrestrial ecosystems, provides a high diversity of niches and abundant food resources [13,41]. We found that all three of these factors were positively correlated with the species number and abundance of waterbirds within a certain range.…”
Section: Factors Affecting Waterbird Habitat Importancementioning
confidence: 99%
“…The population status of such species can, thus, be employed as an indicator in habitat importance assessment. As a number of environmental factors directly affect the survival strategies of waterbirds and determine their habitat selection [12], an understanding of the relationship between these factors and habitat importance is fundamental for devising effective management strategies [13]. A further important conservation approach is to identify protection gap areas by overlaying the distributions of important habitats and protected areas using spatial analysis tools [14,15].…”
Section: Introductionmentioning
confidence: 99%